Optimization of Violations Handling by the Turjawali Unit to Reduce the Rate of Traffic Accidents in the Jurisdiction of the Klaten Regional Police Station - Alifka, Muhammad Fauzi Nur (Advances in Police Science Research Journal, 2024)
This research focuses on efforts to reduce the number of traffic accidents through the prosecution of violations by the turjawali unit of the Klaten Police Traffic Unit. The number of traffic violations recorded is not proportional to the number of traffic accidents which are actually increasing. Traffic accidents essentially occur starting with traffic violations. Therefore, the police are obliged to regulate and maintain traffic safety and order. The purpose of this research is to describe how the implementation of enforcement of violations by the turjawali unit and describe how the organizational resources of the turjawali unit in order to reduce the number of traffic accidents in the jurisdiction of Klaten Police. The approach used in this research is a qualitative approach with field studies so that the author can directly obtain data from observations and interviews. In the conceptual literature, the author uses the concept of optimization, the concept of law enforcement, and the concept of traffic accidents. The theory that the author uses to serve as a problem-solving analysis knife is George R Terry’s management theory and SWOT Analysis Theory. The facts on the ground prove that there are still shortcomings in the prosecution of traffic violations by the unit turjawali satlantas Klaten Police. It can be concluded that, the implementation of enforcement of violations carried out by the unit turjawali satlantas Klaten Police is currently using the E-Tilang method. This method uses ETLE Mobile or by capturing traffic violations. As a result, many invisible violations cannot be crossed using ETLE Mobile. In addition, there are several internal and external factors that support or hinder efforts to prosecute traffic violations in order to reduce the number of traffic accidents in the jurisdiction of Klaten District Police.